삼중블록 고분자 계면활성제의 재유화 억제 기능을 이용한 지속내수성 O/W 에멀젼형 자외선 차단용 화장품 개발 - 이지현; Ji Hyun Lee; 홍성윤; Sung Yun Hong; 이진용; Jin Yong Lee; 안소연; So Youn An; 이효진; Hyo Jin Lee; 김성용; Sung Yong Kim; et al. (大韓化粧品學會誌, 2019)
본 연구는 poly(ethylene glycol)-poly(ε-caprolactone)-poly(ethylene glycol) (PEG-PCL-PEG) 삼중블록 고분자 계면활성제를 이용하여 제조된 우수한 사용감과 선택적인 클렌징 효과를 갖는 수중유(O/W) 에멀젼 타입의 내수성 자외선 차단 제형에 관한 것이다. 수영, 등산 등 다양한 야외 레저 활동이 많아짐에 따라 내수성 자외선 차단제의 수요가 증가하고 있다. 내수성 자외선 차단제는 물이나 땀에 지워지지 않아야하기 때문에 대부분 유중수(W/O) 에멀젼 제형으로 만들어진다. 하지만, W/O 에멀젼 제형은 오일리한 사용감과 클렌징이 어렵다는 단점이 있다. 이에 비해 O/W 에멀젼 제형은 사용감이 우수하고, 클렌징도 용이하지만, 물과의 재유화가 쉽기 때문에 내수성 특성을 갖는 것이 매우 어렵다. 본 연구에서는 이러한 문제를 해결하기 위해 O/W 에멀젼 제형의 HLB 값(~ 10)을 가지면서도 상대적으로 높은 계면장력을 가짐으로써 재유화에 강한 삼중블록 고분자 계면활성제를 도입하였고, 이를 통해 O/W 에멀젼형 지속내수성 자외선 차단제를 개발하였다. 본 연구를 통해 개발된 자외선 차단제는 우수한 사용감과 지속내수성, 그리고 폼 클렌저와의 선택적인 클렌징 효과를 보여준다. 향후 사용감이 다양화된 새로운 O/W 에멀젼형 자외선 차단제 제품 개발에 도움이 될 것으로 기대된다. This study reports water-resistant oil-in-water (O/W) emulsion-based sunscreening formulations prepared using a poly(ethylene glycol)-poly(ε-caprolactone)-poly(ethylene glycol) (PEG-PCL-PEG) triblock polymeric surfactant. As a result of a variety of outdoor recreational activities such as swimming and hiking, consumer needs for development of advanced water-resistant sunscreen formulations are increasing. Water-resistant sunscreens are mostly based on water-in-oil (W/O) emulsions, because they should not be wiped off by water or sweat. However, the W/O emulsion formulations have a disadvantage in that the feeling of use is oily and difficult to remove. On the other hand, the O/W emulsion formulations are excellent in achieving the better skin feel as well as the easier removal. However, it is difficult to provide the O/W emulsion formulations with the water-repelling performance, since re-emulsification likely occurs upon getting touch with water. To solve this problem, this study proposes a O/W emulsion-based sunscreen formulation, a triblock polymeric surfactant having relatively high interfacial tension HLB value (~ 10). This allows the sunscreen formulations to exhibit the improved water repellence function by preventing their re-emulsification. The sunscreen formation system prepared in this study would be useful for diversification of functional sunscreen products, taking advantages of its excellent emulsion stability, UV protection performance, long lasting water-resistant function and selective cleansing effect with only foam cleanser.